2015
DOI: 10.1515/acph-2015-0012
|View full text |Cite
|
Sign up to set email alerts
|

Release of rosmarinic acid from semisolid formulations and its penetration through human skin ex vivo

Abstract: The aim of this study was to evaluate the release of rosmarinic acid (RA) from the experimental topical formulations with the Melissa officinalis L. extract and to evaluate its penetration through undamaged human skin ex vivo. The results of the in vitro release study showed that higher amounts of RA were released from the emulsion vehicle when lemon balm extract was added in its dry form. An inverse correlation was detected between the released amount of RA and the consistency index of the formulation. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…In vitro study of released RA is an informative tool for the assessment of the suitability of the base as a carrier for the insertion of liquid lemon balm extract. Scientific studies have shown that RA was accumulating in the epidermis, and the hydrophilic dermis acted as a barrier preventing deeper penetration and entry of RA into systemic blood flow [ 19 ]. Substance penetration into or through the skin occurs in a coherent sequence when dissolved molecules released from the dosage form reach the surface of the stratum corneum and penetrate through it [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro study of released RA is an informative tool for the assessment of the suitability of the base as a carrier for the insertion of liquid lemon balm extract. Scientific studies have shown that RA was accumulating in the epidermis, and the hydrophilic dermis acted as a barrier preventing deeper penetration and entry of RA into systemic blood flow [ 19 ]. Substance penetration into or through the skin occurs in a coherent sequence when dissolved molecules released from the dosage form reach the surface of the stratum corneum and penetrate through it [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…In vitro release testing identifies the influence of a number of physicochemical parameters such as solubility of the drug substance in the carrier or the effect of particle size and viscosity of the dosage form on the release of the medicinal substance from the dosage form through a synthetic membrane into the acceptor medium [ 17 , 18 ]. The results of scientific research revealed that rosmarinic acid is more easily released from emulsion bases than from ointments [ 19 ]. Because of the lack of data of biopharmaceutical scientific tests, it is important to assess the rate of RA release from modulated hydrophilic gels.…”
Section: Introductionmentioning
confidence: 99%
“…For cosmetic purposes, aiming the development of anti‐ageing skin products, the main advantage related to lipid‐based nanotechnology delivery systems is precisely its ability to penetrate the skin layers . In the literature, only one study described the cutaneous permeation of semisolid formulations containing M. officinalis L. extract in human skin, this is the first time that this application was reported for lipid‐nanotechnology‐based delivery systems containing RA thickened in hydrogels.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, for topical application, the low viscosity from nanoemulsions is a concern and the design of a semisolid formulation is a key consideration. In the literature, only one study described the development of semisolid formulations containing Melissa officinalis L. extract for topical application and did not use nanotechnology‐based products for the improvement of RA skin retention/permeation …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation